O Tribunal de Contas e a “carona” no sistema de registro de preços: possibilidade de adesão tardia por empresas estatais em propostas vantajosas - Blanchet, Luiz Alberto (Universidad Nacional del Litoral, 2016)
State companies have clear importance in promoting the development of society. In possession of legal regime of private law with exceptions under public law, their contracts are subject to the bidding process. After implementing the use of the Price Registration System, provided in article 15, II, of Law nº 8.666/93, emerged the figure of the late accession, commonly called “carona” or "ride". Initially envisaged by Decree nº 3.931/2001, this institute quickly gained followers in the different areas of public administration, which attracted the attention of the Audit Court of the Union, which tried, especially by the judgments n. 1.487/2007 and n. 1.233/2012 limit the use of the ride. Due to the various constraints imposed by the Court of Auditors, late accession fell into disuse, until the issuance of Decree nº 7,892/2013. With the new regulation, rules previously considered obscure by the TCU were reformulated, legitimizing the use of ride procedure in prices registry protocol managed by other public agencies. In this context, the research aims to identify the fundamentals – principles and legal – so that state companies can join lately in prices registry system in a safe way, obtaining the most advantageous proposal for the interest body, provided certain requirements.